ANALYSIS OF LEGAL SCIENCE'S VIEWS ON THE OBLIGATION OF COMMUNITY GARDEN DEVELOPMENT (PLASMA GARDEN) IN PLANTATION COMPANIES AS A MANDATE OF THE PRINCIPAL AGRARIAN LAW - Juda Deo Silitonga; Maria Kaban; Rosnidar Sembiring (PT. Radja Intercontinental Publishing, 2024)
The obligation to provide plasma plantations is also one of the requirements for obtaining land rights in the form of Cultivation Rights (HGU) by the Company, as stipulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia No. 7 of 2017 concerning Regulations and Procedures for Determining Cultivation Rights, which in Article 40 letter (k) and Article 41 states: